Circadian Rhythm Modulates the Therapeutic Activity of Pulsed Electromagnetic Fields on Intervertebral Disc Degeneration in Rats. (25th March 2022) - Zheng, Yi; Hao, Yiming; Xia, Bing; Mei, Liangwei; Li, Shengyou; Gao, Xue; Ma, Teng; Wei, Bin; Tan, Zhifen; Lan, Pingheng; Luo, Zhuojing; Jing, Da; et al.
Abstract : Circadian rhythm (CR) imparts significant benefits in treating multiple diseases, such as heart diseases and arthritis. But the CR effect on intervertebral disc degeneration (IVDD) therapy remains unclear. Recent studies revealed that pulsed electromagnetic fields (PEMF) are capable of alleviating IVDD. In this study, we evaluated the CR-mediated regulation of PEMF therapeutic effect on IVDD induced by rat tail disc needle puncture. Our results demonstrated that the daytime PEMF stimulation (DPEMF) is more effective than the nighttime PEMF (NPEMF) in delaying IVDD. Moreover, the rats treated with DPEMF maintained better disc stability and histology after 8 weeks, relative to NPEMF. CR and PEMF cotherapies were also examined in cellular models, whereby serum shock was used to induce different levels of clock gene expression in the nucleus pulposus (NP), thus imitating CR in vitro . PEMF at ZT8 (higher level of clock gene expression) correlated with a higher extracellular matrix (ECM) component expression, compared to ZT20 (lower level of clock gene expression). Taken together, these data suggest a strong role of CR in regulating the beneficial effect of PEMF on IVDD. Our findings provide a potential clinical significance of CR in optimizing PEMF positive effects on IVDD.